Bilateral Herpes Simplex Uveitis: Review of the Literature and Own Reports? (2017)
Purpose: Herpes simplex-associated uveitis is usually considered a unilateral eye disease, and rarely included in the differential diagnosis whenever there is bilateral involvement. We report three cases of bilateral herpetic anterior uveitis. Methods: We evaluated three patients who presented with clinical manifestations of bilateral uveitis suggestive of viral origin. Results: We found intraocular hypertension, cells in the anterior chamber, paralytic mydriasis, iris atrophy with transillumination defects, and variable anterior vitreous cellularity. According to the clinical findings, supported with herpes-specific antibody titers and aqueous humor PCR results in two of them, they were diagnosed with bilateral anterior herpetic uveitis. Conclusions: Our patients were initially misdiagnosed as having non-infectious uveitis and were treated with immunomodulatory medications, which could have favored the extension of infection bilaterally. Although uncommon, bilateral herpetic uveitis should always be considered in the differential diagnoses, when patients present with hypertensive uveitis in both eyes. © Taylor and Francis Group, LLC.